2018
DOI: 10.1002/ss.20259
|View full text |Cite
|
Sign up to set email alerts
|

Using the Social Class Worldview Model in Student Affairs

Abstract: This chapter explores social class myths, the Social Class Worldview Model, and suggestions for student affairs professionals to facilitate social class identity development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our examination of qualitative and mixed methods research confirmed and furthered existing research on food insecurity (Broton & Goldrick‐Rab, 2018; Hallett et al., 2019) and attended to calls to embrace subjectivity in social class research (Garrison & Liu, 2018; Liu, 2011; Liu et al., 2004; Rubin et al., 2014; Soria, 2018). Quantitative researchers have found that students often face other forms of basic needs insecurity in addition to food insecurity, most notably housing insecurity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our examination of qualitative and mixed methods research confirmed and furthered existing research on food insecurity (Broton & Goldrick‐Rab, 2018; Hallett et al., 2019) and attended to calls to embrace subjectivity in social class research (Garrison & Liu, 2018; Liu, 2011; Liu et al., 2004; Rubin et al., 2014; Soria, 2018). Quantitative researchers have found that students often face other forms of basic needs insecurity in addition to food insecurity, most notably housing insecurity.…”
Section: Discussionsupporting
confidence: 73%
“…Further, quantitative studies limit the exploration of broad conceptualisations of students' social class identities, often oversimplifying class identity by focusing on seemingly objective measures such as income or wealth and education level, which are only part of the lived experience of social class (Martin & Elkins, 2018;Soria, 2018). Garrison and Liu (2018) argued that researchers should 'ask about [research subjects'] internal understanding of social class' (p. 20) because social class is inherently subjective, fluid and omnipresent (Liu, 2011;Liu et al, 2004;Soria, 2018). Moreover, Rubin et al (2014) asserted that subjective…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2004) social class worldview model (SCWM) demonstrates how social class incorporates economics, but also relates to an individual's values and beliefs about their class culture and how they make sense of "the demands and expectations of their economic culture and maximize their opportunities to accumulate the valued capital within that economic culture" (p. 104). As argued by Ardoin and martinez (2019), defining social class is complex, subjective, and cannot be reduced to component parts (economic status, employment, or educational attainment), but rather is an everfluctuating amalgamation of all three (Loh Garrison & Liu, 2018). Class identity is foundational and fluid, shifting in saliency according to one's environment, organizational placement, current economic standing, and community of origin.…”
Section: First-generation College Students and Social Classmentioning
confidence: 99%
“…Leadership educators must challenge the dominant narrative of the prototypical leader as well as social identity biases. For example, not all poor and working-class students aspire to society's upward mobility bias and feel more connected to their working-class values (e.g., dignity, resourcefulness, and self-reliance) (Garrison & Liu, 2018). Instead, leadership educators should elevate the voices and ideas of those most intimately connected to the oppression that socially just leadership education tries to address.…”
Section: Challenging the Dominant Narrative Leadership By Centering Mmentioning
confidence: 99%